Effectiveness of the "healthy life" educational strategy to promote newborn care (Kristen Swanson's theory) in Andean adolescent mothers of Peru (GnosisWisdom, 2022)
Introduction. Newborn health has gained increasing relevance on the public agenda, so the strategies are aimed at promoting favorable environments for neonatal health, through strengthening the approach in the community.Objective. Estimate the effectiveness of the "Vida sana" educational strategy to promote newborn care in adolescent mothers, applying Kristen Swanson's Theory in the rural area of Huancavelica.Methodology. The study was explanatory, the research design was pre-experimental with a single group before and after. The sample consisted of Andean adolescent mothers with newborns (n=25) considering the inclusion and exclusion criteria. For data collection, the survey technique was used, whose validated instruments such as the questionnaire to demonstrate the variables of newborn care by adolescent mothers.Results. Before the intervention, 60.0% of adolescent mothers in general terms report knowing little about newborn care, 24.0% do not know. Moments later, 64.0% manage to know about newborn care, 32.0% manage to know little and even 4.0% are unaware. It is concluded that the application of the educational strategy generates cognitive changes in people to improve care in the newborn, considered a very vulnerable group in extrauterine life.Conclusions. The educational strategy was effective in improving newborn care in rural areas.
Keywords: Newborn; neonate; home newborn care; kangaroo mother care